Plocamium pusillum Sonder Intertidal 1845 - Huisman, John M.; Saunders, Gary W. (Zenodo, 2021)
Plocamium pusillum Sonder Botanische Zeitung 3: 54 (Sonder 1845). TYPE LOCALITY. — ad oras occidentales Novae Hollandiae. The type specimen was epiphytic on a stem of Amphibolis . LECTOTYPE (here designated). — MEL 1005815 (Fig.2). Note: Sonder (1845) did not cite a specific specimen, but later (1846) gave ‘ Herb. Preiss No. 2613’. This number does not appear on MEL 1005815, which may suggest the existence of additional specimens in other herbaria. However, since we are unaware of any further specimens, we herein lectotypify the species with the single MEL specimen. SPECIMENS EXAMINED (DNA sequence vouchers). — Western Australia , First Rock, S of Penguin Island, Shoalwater Marine Park, 15.II.2011, J.Huisman 15.2.11.1.16 (PERTH 08715351); Cape (Point) Peron, W.A., 3 m depth on algae, G.W.Saunders & K.Dixon (UNB, GWS025286); New South Wales: Yellow Rock, Lord Howe Island, from 15 m depth on rock, G.W.Saunders (UNB, GWS002025); Victoria: The Springs, Point Lonsdale, 4 m depth on rock, G.W.Saunders & L.Kraft (UNB, GWS016698); Norfolk Island, 1 m depth on rock, G.W.Saunders & K.Dixon (UNB, GWS029289). ADDITIONAL SPECIMENS EXAMINED (unsequenced, based on morphology). — Western Australia , Cape Peron, epilithic, 25.II.2021, J.M.Huisman (PERTH 09316647); Eglinton Rocks, 17.V.1996, J.Huisman JH 665 (PERTH 06546757); Burns Beach, drift, 2.IX.1985, R.D.Royce 2562 (PERTH 05163587); Cottesloe, drift, 12.VI.1951, R.D.Royce 1062 (PERTH 04017765); Capel Beach, on rocks between tides, 17.IX.1949, R.D.Royce 368 (PERTH 04017862); Point [Cape] Peron, epiphytic, 28.V.1949, R.D.Royce s.n. (PERTH 04017870); Mushroom Rock, Thomson Bay, Rottnest Island, 16.X.1934, A.Nash s.n. (PERTH 04017838). DISTRIBUTION. — Based on molecular analyses, this species is widely distributed and known from southern Western Australia, Victoria, and New South Wales (Lord Howe Island) and Norfolk Island. HABIT. — Thallus (Fig. 3A) dark red, to 6 cm tall, much branched, attached by a hapteroid holdfast to seagrasses, algae or epilithic ...